Correlation Between Histopathologic, Arthroscopic, and Magnetic Resonance Imaging Findings in Dogs With Medial Coronoid Disease. Issue 4 (16th September 2014) - Wavreille, Vincent; Fitzpatrick, Noel; Drost, Wm Tod; Russell, Duncan; Allen, Matthew J.
<x xml:space="preserve">Abstract</x> Objective To describe the magnetic resonance imaging (MRI), arthroscopic, and histopathologic changes in dogs with medial coronoid disease and to identify potential relationships between these findings. Study Design Retrospective case series. Sample Population Twenty‐five diseased medial coronoid processes (MCP) were collected from 19 dogs with a confirmed diagnosis of medial coronoid disease that were surgically treated by subtotal coronoid ostectomy. A reference group of normal MCP was collected from 9 dogs euthanatized for reasons unrelated to elbow disease. Methods MCP specimens were evaluated by MRI using a novel grading scheme (all dogs), arthroscopy using a modified Outerbridge scheme (affected dogs only) and histopathology (all dogs). Results The common histopathologic findings were subchondral microfractures, subchondral microfractures continuous with cartilaginous fissures, moderate to severe hypercellularity of the marrow space, trabecular bone necrosis, and articular cartilage degeneration. The severity of cartilage disease in the MCP was moderate to severe in most specimens, even in cases with minimal arthroscopic pathology. Three distinct patterns of bone marrow lesion (BML) were identified adjacent to the MCP, but there was no correlation between BML pattern and either histopathologic or arthroscopic findings. There was moderate correlation between modified Outerbridge scores and MRI scores. No correlation was identified between the histopathologic changes and either MRI or arthroscopic scores. Conclusion There was no significant correlation between the clinical scores and histopathologic changes. Ongoing improvements in the resolution of noninvasive imaging techniques will likely improve description and understanding of the MCP disease in dogs.